KEANEKABAHASAAN DAN PENGEMBANGAN KARAKTER DARI PERSPEKTIF PENDIDIKAN MULTIKULTURAL - Simon Sabon Ola; Tince Taela Margarita Nenoliu; Liski A.Th. Subu Taopan; Paulina Maria Yovita Kosat; Yohanes Adventura LB. Lamawato (Jurnal Lazuardi, 2021)
This article discusses the development of character, awareness of diversity and multicultural education. Characters cannot be developed through slogans, rhetoric, or lectures, through various activities that are natural in nature which indicate various attitudes, values ​​and characters. One activity that requires the use of language in a variety of grammar communities.Talks about people with various languages ​​cannot be returned from the question of diversity (multiculturalism). Regarding the rights of each language and taking its speakers, a multicultural perspective is needed to address differences in social interactions and cultural interactions. The agreed interaction process allows the formation of norms and values ​​that lead to the formation of character.Based on observing the situation of diversity with various characteristics, it can characterize that can be developed and developed from the situation of diversity. These characters were identified through various language typologies, various repertoires, awareness about motherhood, dynamic diglossia, characteristics of language choice, the role of Indonesian in multiculturalism perspective. Approved characters, among others: agreed, mutually agreed, social care, religious, national spirit and love of the motherland. Thus, diversity can be a medium of education and character development in the development of multiculturalism.